2016
DOI: 10.1007/s00340-016-6611-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase-stable, multi-µJ femtosecond pulses from a repetition-rate tunable Ti:Sa-oscillator-seeded Yb-fiber amplifier

Abstract: 400 kHz, which to the best of our knowledge corresponds to the highest phase stability ever demonstrated for highpower, multi-MHz-repetition-rate ultrafast lasers. This system will enable experiments in attosecond physics at unprecedented repetition rates, it offers ideal prerequisites for the generation and field-resolved electro-optical sampling of high-power, broadband infrared pulses, and it is suitable for phase-stable white light generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Figure a shows the CEP shift of both the input signal and the output of the OPA as obtained by means of an f‐to‐2f interferometer operated with 4 ms integration time over a period of 10 s. The resulting RMS standard deviation after the OPA is 19.3 mrad. The power spectral density of the CEP noise up to 125 Hz (Figure b) compares positively with other systems providing high pulse energy at high repetition rate . This value represents a marginal increase as compared to the seed (12.3 mrad) that is mainly attributed to nonlinear phase shifts in the f‐to‐2f interferometer itself as a result of minor fluctuations in amplitude.…”
Section: Intense Few‐cycle Pulses At High Repetition Ratesupporting
confidence: 55%
See 1 more Smart Citation
“…Figure a shows the CEP shift of both the input signal and the output of the OPA as obtained by means of an f‐to‐2f interferometer operated with 4 ms integration time over a period of 10 s. The resulting RMS standard deviation after the OPA is 19.3 mrad. The power spectral density of the CEP noise up to 125 Hz (Figure b) compares positively with other systems providing high pulse energy at high repetition rate . This value represents a marginal increase as compared to the seed (12.3 mrad) that is mainly attributed to nonlinear phase shifts in the f‐to‐2f interferometer itself as a result of minor fluctuations in amplitude.…”
Section: Intense Few‐cycle Pulses At High Repetition Ratesupporting
confidence: 55%
“…The power spectral density of the CEP noise up to 125 Hz (Figure 3b) compares positively with other systems providing high pulse energy at high repetition rate. [27][28][29][30] This value represents a marginal increase as compared to the seed (12.3 mrad) that is mainly attributed to nonlinear phase shifts in the f-to-2f interferometer itself as a result of minor fluctuations in amplitude. An extended characterization of the passive phase locking scheme of the driving laser suggests that the CEP noise integrated from the Nyquist-frequency (half the OPA output repetition rate, i.e.…”
Section: Intense Few-cycle Pulses At High Repetition Ratementioning
confidence: 88%
“…For waveform-stable IAPs, first of all it is a requirement that the enhanced comb has an offset frequency of zero. This can be accomplished by phase-stabilizing the seeding comb [22,28,29] and using tailored cavity mirrors [30]. Then, the XUV emission must be confined to only one attosecond burst per pulse.…”
Section: State Of the Art Of Hhg In Femtosecond Ecsmentioning
confidence: 99%
“…Therefore, the predicted photon flux should be regarded as a rather strong underestimation of the flux attainable with implementing this scheme at a repetition rate at which each gas atom is hit by a single pulse only. With state-of-the-art lasers operating at the highest repetition rates in this regime [29] and a pulse-energy-scalable compression scheme (e.g. [67]), the seed pulse energy can be increased accordingly.…”
Section: Photon Flux Estimation For Tmgmentioning
confidence: 99%
“…For the case of the high average power compression experiments outlined above, a CEP stable fiber chirped pulse amplification system is required. Current research efforts showed that this requires synchronized radio‐frequency drivers for the employed acousto‐optical pulse pickers resulting in the recent demonstration and stabilization of a 80W, μJ‐level fiber CPA system with subsequent nonlinear compression to 30fs and less than 100 mrad CEP noise . These results should pave the way for achieving >100W, sub‐2 cycle pulses with stabilized CEP and high energy.…”
Section: Nonlinear Pulse Compression To Few‐cycle Durationsmentioning
confidence: 99%